A cross-sectional study on the association of level of Vitamin D with severity of fibromyalgia syndrome in a tertiary care hospital, Kolkata - Mausumi Sen; Sulagna Das; Santanu Sen; Nabanita Baidya Biswas; Tanmoy Naskar; Swapan Kumar Mishra; Swati Bhattacharyya (Asian Journal of Medical Sciences, 2024)
Background: Fibromyalgia (FM) is a chronic disorder characterized by widespread pain associated with fatigue, stiffness, sleep disturbance, cognitive dysfunction, anxiety, and depression. The role of Vitamin D in the pathophysiology of FM is poorly known. Studies available to establish the association between Vitamin D and FM have inconsistent results. Some of the studies reported a positive association and others found no relation. It is not clear whether the pain is due to and/or associated with low levels of Vitamin D. Aims and Objectives: The objective of the current study is to estimate Vitamin D levels in FM patients and to find the association between Vitamin D levels and severity of FM. Materials and Methods: In this cross-sectional study, seventy patients who fulfilled the inclusion (American College of Rheumatology 2016 criteria) and exclusion criteria as has been considered for the study were enrolled and their serum 25 hydroxy-vitamin D level has been measured by enzyme-linked immunosorbent assay reader. Pre-designed questionnaires were prepared to measure FM severity. Pain intensity was measured by the Visual Analog Scale (VAS). Results: A total of 70 patients who were diagnosed with FM were included in our study. The majority of them (80%) were female and the rest (20%) were male. The mean age is 48.2±9.2 years. Their mean body mass index (BMI) is 23.7±3.82. The mean Vitamin D serum level was 22.4±9.2 ng/dL. Vitamin D deficiency (VDD) was defined as patients with a serum level of 20 ng/mL and below. In our study, 62.8% (44) of the study population had VDD. According to VAS (0–10) pain scale, 15 (21.4%) subjects suffered from moderate pain and 55 (78.6%) subjects suffered from severe pain. The severity of FM was measured by the Fibromyalgia Severity Scale (FSS). The mean score of FSS was 22.7. To find the association between VDD and severity of FM, several covariates were identified and a multivariable logistic regression was done. Conclusion: VDD increases with an increase in age, BMI, VAS, and FSS, all of which are predicators of FM syndrome.